Peran Profitabilitas dalam Memoderasi Pengaruh ESG, Leverage, dan Related Party Transactions terhadap Tax Avoidance - Anggraini, Vanda Dwi; Jannah, Richatul (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study examines the determinants of tax avoidance among Indonesian manufacturing firms by focusing on ESG disclosure score, Leverage, and Related Party Transactions, while incorporating Return on Assets (ROA) as a moderating variable. Using 108 firm-year observations from companies listed on the Indonesia Stock Exchange during 2021–2023, the analysis applies panel data regression and moderated regression analysis (MRA). The findings reveal that ESG disclosure score has a negative and significant effect on tax avoidance, indicating that higher ESG transparency is associated with lower levels of tax avoidance. In contrast, Leverage and Related Party Transactions do not show significant effects in the baseline model. ROA is found to have a negative significant effect on tax avoidance and moderates the relationships between ESG disclosure score and Related Party Transactions with tax avoidance, but does not moderate the effect of Leverage. These results highlight the role of profitability in shaping the relationship between corporate characteristics and tax behavior.